Mitotically Active Plexiform Fibrohistiocytic Tumor. (27th March 2013) - Zemheri, Ebru; Özkanlı, Şeyma; Şenol, Serkan; Ozen, Filiz; Ulukaya Durakbaşa, Cigdem; Zindancı, İlkin; Okur, Hamit
Abstract : Plexiform fibrohistiocytic tumor is an intermediate malignant tumor situated in superficial soft tissues. It affects children and young adults. The tumor is most commonly located on upper extremities, whereas involvement of back region is rare. Mitotic activity is generally low (~3/10 HPF). It is rare, but it can exhibit aggressive behavior, so total excision with clear surgical margins and long-term followup is necessary to detect local recurrence and metastases. We report a child with a solid mass on back region which was found to be a mitotically active plexiform fibrohistiocytic tumor (6/10 HPF) after excision. Plexiform fibrohistiocytic tumor (PFT) is a mesenchymal neoplasm of children, adolescents, and young adults. It is characterized by fibrohistiocytic cytomorphology and multinodular growth pattern. Clinically it is usually a slow-growing mass of upper extremities with frequent local recurrence and rare regional lymphatic and systemic metastasis (Fletcher et al. (2002), Enzinger and Zhang (1988), Remstein et al. (1999)).